Ambition and the Bleak Legacy of Liberal Thought in Benito Pérez Galdós' La Fontana de Oro: Novela histórica (1871). - Cameron, Bryan (Romance Notes, 2024)
Re-reading Benito Pérez Galdós' La Fontana de Oro as an archive of resentments directed at Church and monarchic hegemony in nineteenth-century Spain, I analyze the defeat of the protagonist's political ambitions during the Liberal Triennium (1820-1823). This essay moves away from previous scholarship that interprets the text as a lesson in moderation by focusing on Lázaro's expulsion from the world of politics and the negative affects that surface due to his defeat in either of the novel's conclusions. I also place La Fontana de Oro within a Western tradition of "literary liberalism" that acknowledges the contradictions between progressive politics and a "bleak" vision of a society unable to assimilate them fully (Anderson 48). Examining ambition as a nascent experience for young men such as Lázaro, who dream of toppling the pillars of the Ancien Régime , I point to the ambivalence underpinning the novel and its ambiguous take on the present and future of liberal thought in modern Spain.